THE TECHNOLOGY READINESS OR SOCIAL PRESENCE, WHICH ONE COULD EXPLAIN THE TECHNOLOGY ACCEPTANCE BETTER? AN INVESTIGATION ON VIRTUAL COMMUNITIES - Said Jubran; Sumiyana Sumiyana (Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
Internet technology has accelerated the development of communities from face-to-face into computer-mediated communications. Individuals who joined the virtual communities contributed greatly to building their knowledge by sharing their experiences. This study investigates the individuals’ knowledge sharing intentions using two approaches for the research model. The first approach is adopted from Hung & Cheng’s (2013) model that incorporates technology readiness, compatibility and acceptance. The second approach is a new model built specifically for this study which combines the social presence and compatibility into the technology acceptance. Furthermore, this study compared both models to identify their ability to explain the individuals’ knowledge sharing intentions.This study’s results show that the first model is not better than the second. In the first model, the technology readiness, as represented only by the innovative, is the only one having a positive effect on the technology acceptance. Meanwhile, the three other constructs, i.e. optimism, discomfort, and insecurity are not. In the second model, the social presence and compatibility that are integrated into the Technology Acceptance Model could actually positively affect the technology acceptance.In the technology readiness model, the ease of the technology is not the indicator which assesses the usefulness of the technology. Meanwhile, in the social presence model, the ease of use affects the usefulness of the technology. Furthermore, both in the technology readiness and social presence models, the perceived usefulness and ease of use affect the knowledge sharing intentions. The study finds that the social presence is able to explain the knowledge sharingintentions better than the technology readiness does. It implies practically that virtual community providers should make individuals be more active in their virtual communities. Then, the providers could facilitate the improvement of the individuals’ cognitive capabilities and competencies with their high motivation for knowledge sharing.Keywords: technology readiness, social presence, communications medium, compatibility, virtual community, online learning